Epidemiological profile of perinatal mental disorders at a tertiary hospital in Yaoundé- Cameroon - Djatche Miafo, Joël; Woks, Namanou Ines Emma; Nzebou, Daniel; Tchaptchet, Idriss; Delene, Suzi Thio; Kegha Tchidje, Orelien; Ndzodo, Gervais; Siewe Kamga, Berthe; Assumpta, Lucienne Bella (Frontiers in Global Women's Health, 2023)
In developing countries, 15.6% of pregnant women and 19.8% after childbirth experience a mental disorder. In the absence of data on the situation in Cameroon, we carried out a study to determine the prevalence of perinatal mental illness in this hospital and its risk factors among women in perinatal period and the relationship between both at the Yaoundé Gynaeco-Obstetric and Paediatric Hospital, a reference mother and child hospital. We conducted a hospital-based, cross sectional, observational study. Data was collected using structured and semi-structured interviews. There were six sub-themes covered: participants’ socio-demographic profile, clinical profile, perinatal history, psychopathology aspects with the Mini International Psychiatric Interview, the Edinburgh Postnatal Depression Scale, the State Trait Anxiety Inventory and the perinatal mental illness risk factors. Data entry was done using Microsoft Excel 2010 and transferred to Statistical Package for the Social Sciences version 23.0 for analysis. Among 194 women who participated in the study, the general prevalence for perinatal mental disorders was 53.6% (104/194), 25.8% among pregnant women and 27.8% among postnatal women. Comorbidities were present in 17.5% of our study population. We observed that 45.8% suffered from depression, 17% had a risk of suicide, 10.3% suffered from perinatal anxiety, 3.1% presented with post-traumatic stress disorder, 3.6% acute stress disorder, 7.7% had adjustment disorder. Concerning risk factors, we found a significant link between depression and severe anxiety before delivery (p < 0.05) and the absence of social support (p = 0.005). We found that women with at least four risk factors were 1.6 times more likely to present with a perinatal mental disorder. The prevalence of perinatal mental disorders at this Hospital is very high. This highlights the need for institutional screening and management of perinatal mental disorders, which suggests that we explore the situation in others and other health facilities in Cameroon.